2010
DOI: 10.1111/j.1476-5381.2010.00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms and drug interactions modulating CYP2D6 and CYP3A activities have a major effect on oxycodone analgesic efficacy and safety

Abstract: Background and purpose:The major drug-metabolizing enzymes for the oxidation of oxycodone are CYP2D6 and CYP3A. A high interindividual variability in the activity of these enzymes because of genetic polymorphisms and/or drug-drug interactions is well established. The possible role of an active metabolite in the pharmacodynamics of oxycodone has been questioned and the importance of CYP3A-mediated effects on the pharmacokinetics and pharmacodynamics of oxycodone has been poorly explored. Experimental approach: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(107 citation statements)
references
References 46 publications
4
100
2
1
Order By: Relevance
“…Different opioids have been applied in studies using the cold pressor test and have been found to be effective. The model was even sensitive enough to separate the effects of different genotypes in the subjects (Eckhardt et al, 2000;Grach et al, 2004;Zwisler et al, 2009Zwisler et al, , 2010Samer et al, 2010). Fentanyl has been tested in the cold pressor test, and this model was sensitive to the analgesia induced.…”
Section: Pharmacology Of Human Pain Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different opioids have been applied in studies using the cold pressor test and have been found to be effective. The model was even sensitive enough to separate the effects of different genotypes in the subjects (Eckhardt et al, 2000;Grach et al, 2004;Zwisler et al, 2009Zwisler et al, , 2010Samer et al, 2010). Fentanyl has been tested in the cold pressor test, and this model was sensitive to the analgesia induced.…”
Section: Pharmacology Of Human Pain Modelsmentioning
confidence: 99%
“…Skin and teeth. Both morphine and oxycodone have been tested against cutaneous heat and cold pain, mechanical (pinching) pain, and electrical pain, and generally these models reflect analgesia from these opioids (Naef et al, 2003;Schulte et al, 2003;Joly et al, 2005;Staahl et al, 2006a;Olesen et al, 2010a;Samer et al, 2010). Three studies found sensitivity of electrical pain for morphine, whereas another did not (Schulte et al, 2003;Joly et al, 2005;Staahl et al, 2006a).…”
Section: B Opioidsmentioning
confidence: 99%
“…the virus, 2 dosing of aminoglycosides based on renal function, 3 or the likelihood of a serious drug-drug interaction based on patient genotype. 4 Training and how to assess or evaluate the statistical and clinical relevance of these differences has historically been limited. It is imperative that medical and pharmacy managers possess relevant knowledge to determine the extent that heterogeneity was evaluated in clinical trials.…”
Section: Educational Program On Heterogeneitymentioning
confidence: 99%
“…In the past decade, research has given us a great amount of knowledge on the genetic disposition that explains these differences, and to what extent people react differently to pain. The opioid receptor and its determining gene (OPRM1) has been shown to have 17 variations (socalled polymorhism) that are unequally distributed between the sexes (Samer, 2010;Kolesnikov, 2011). Women are found to have μ receptor variations that predispose to longer clinical effects of an opioid, and twice as many side effects as men (Sarton, 2003;Niesters, 2010).…”
Section: Gender-specific Pharmacogeneticsmentioning
confidence: 99%